Mapping of the myxomatous mitral valve: The three-dimensional extension of mitral annular disjunction in surgically repaired mitral prolapse - Biondi, Raoul; Ribeyrolles, Sophie; Diakov, Christelle; Amabile, Nicolas; Ricciardi, Gabriella; Khelil, Nizar; Berrebi, Alain; Zannis, Konstantinos (Frontiers in Cardiovascular Medicine, 2022)
Objectives This study aimed to describe the heterogeneous extension of mitral annular disjunction (MAD) and assess the hypotesis that different phenotypes of disjunction are not associated with increased surgical challenges. Background Mitral regurgitation (MR) is the most common end-stage scenario of degenerative mitral valve disease (DMVD). Few data exist on the three-dimensional extension and geometry of MAD, as well as for its role in valvular dynamic and coaptation. Methods A total of 85 consecutive subjects, who underwent elective mitral valve repair (MVR) for MMVD at our Institution between November 2019 and October 2021, were studied retrospectively. The extension and geometry of MAD was assessed using the digitally stored volumetric datasets of real-time 3D transesophageal echocardiography (TEE). Annular phenotypes and surgical repair techniques were analyzed. Results Mitral annular disjunction was diagnosed in 50 out of 85 patients (59%) with Barlow disease (BD). A detailed analysis of MAD extension was conducted on 33 patients. Two pattern of disjunction were identified: a bimodal shape was highlighted in 21 patients, while a more uniform distribution of the disjuncted annulus was observed in 12 patients. The bimodal pattern was characterized by lower disjunction distance (DD) at the 140°–220° arch (3.6 ± 2.2 mm), while a more regular DD was measured in the remaining patients. All patients successfully underwent MVR. Triangular leaflet resection was performed in 58% of the cases, neochordae implantation in 9%, and notably a 27% received an isolated annuloplasty. Conclusion Rather than a binary feature, MAD should be taken into account in its complex and heterogeneous morphology, where two major phenotypes can be identified. Despite its anatomical complexity, MAD was not associated with an increased surgical challenge; conversely a peculiar subgroup of patient was successfully treated with an isolated annuloplasty.